2018
DOI: 10.1038/s41598-017-18506-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antimicrobial resistance genes associated with the International Space Station environmental surfaces

Abstract: Antimicrobial resistance (AMR) is a global health issue. In an effort to minimize this threat to astronauts, who may be immunocompromised and thus at a greater risk of infection from antimicrobial resistant pathogens, a comprehensive study of the ISS “resistome’ was conducted. Using whole genome sequencing (WGS) and disc diffusion antibiotic resistance assays, 9 biosafety level 2 organisms isolated from the ISS were assessed for their antibiotic resistance. Molecular analysis of AMR genes from 24 surface sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 48 publications
1
103
1
1
Order By: Relevance
“…Spaceflight could affect the drug resistance phenotype of bacteria and a profound drug resistance capacity of ISS microorganisms against environmental stresses was detected during these years (Mora et al, ; Singh et al, ; Urbaniak et al, ). It has been demonstrated that the increased antibiotic tolerance of Escherichia coli in human spaceflight environment might be attributed to the upregulation of genes related to oxidative stress response (Aunins et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spaceflight could affect the drug resistance phenotype of bacteria and a profound drug resistance capacity of ISS microorganisms against environmental stresses was detected during these years (Mora et al, ; Singh et al, ; Urbaniak et al, ). It has been demonstrated that the increased antibiotic tolerance of Escherichia coli in human spaceflight environment might be attributed to the upregulation of genes related to oxidative stress response (Aunins et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Red spots represent upregulated genes, blue spots represent downregulated genes, and gray spots represent the genes that did not change significantly F I G U R E 7 Hierarchical clustering analysis of DEGs for the SEG and SES strains. Blue bars represent the downregulated genes, red bars represent the upregulated genes, and white bars represent the genes that did not change significantly Spaceflight could affect the drug resistance phenotype of bacteria and a profound drug resistance capacity of ISS microorganisms against environmental stresses was detected during these years (Mora et al, 2016;Singh et al, 2018;Urbaniak et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other publications also focused on the detection of antimicrobial resistance genes aboard the ISS and evaluated the potential risk these genes might represent in a closed spacecraft environment (20). Singh et al assessed the succession and persistence of microbial communities and the associated antimicrobial resistance and virulence properties based on metagenomic reads obtained from samples of three flights.…”
Section: Introductionmentioning
confidence: 99%
“…From this panel, we only used the first primer pool targeting the ARGs. The second panel used was the Ion AmpliSeq™ Antimicrobial Resistance (AMR) Research panel that also consisted of two primer pools comprising a total of 815 amplicons targeting 478 known ARGs 32 . Both primer pools were used from this panel.…”
Section: Methodsmentioning
confidence: 99%